Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1186/s10194-022-01410-2
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated alpha oscillation and hyperresponsiveness reveals impaired perceptual learning in migraineurs

Abstract: Background Anomalous phantom visual perceptions coupled to an aversion and discomfort to some visual patterns (especially grating in mid-range spatial frequency) have been associated with the hyperresponsiveness in migraine patients. Previous literature has found fluctuations of alpha oscillation (8-14 Hz) over the visual cortex to be associated with the gating of the visual stream. In the current study, we examined whether alpha activity was differentially modulated in migraineurs in anticipat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 103 publications
2
4
0
Order By: Relevance
“…Another study included 28 migraine patients (17 with aura/11 without) and 29 non-migraine patients and compared the power of alpha during and before and after the visual stimulus and found that in migraineurs before stimulus onset, alpha power was significantly reduced relative to controls, indicating that migraine patients have alpha defects in the prophase of visual stimulation. Given that alpha activity is related to functional inhibition of the sensory cortex, the present study is consistent with the notion that migraine patients have a hyperresponsive visual cortex (Fong et al, 2022).…”
Section: Figuresupporting
confidence: 90%
See 1 more Smart Citation
“…Another study included 28 migraine patients (17 with aura/11 without) and 29 non-migraine patients and compared the power of alpha during and before and after the visual stimulus and found that in migraineurs before stimulus onset, alpha power was significantly reduced relative to controls, indicating that migraine patients have alpha defects in the prophase of visual stimulation. Given that alpha activity is related to functional inhibition of the sensory cortex, the present study is consistent with the notion that migraine patients have a hyperresponsive visual cortex (Fong et al, 2022).…”
Section: Figuresupporting
confidence: 90%
“…Changes in EEG frequency bands have been commonly observed. Compared with healthy controls, the main alpha band abnormalities found were the slowing and asymmetry of the dominant frequency (Nyrke et al, 1990;de Tommaso et al, 1998;O'Hare et al, 2018), different brain region alpha increases or decreases in activity (Clemens et al, 2008;Bjork et al, 2009a;Ojha and Panda, 2022), alpha oscillatory fluctuations, particularly on tasks relying on temporal integration (O'Hare et al, 2018), visual stimuli (Fong et al, 2022), and noxious/nonnoxious stress (Rainero et al, 2001), etc. Some studies have shown different changes in low-frequency power (e.g., delta and theta frequency bands) (Bjork et al, 2009a(Bjork et al, , 2011bOjha and Panda, 2022) ADDIN.…”
Section: Eeg Features Of Migraine and The Subtypesmentioning
confidence: 99%
“…50,51 The α rhythm is related to functional inhibition of the sensory cortex and might represent the GABAergic inhibitory feedback paced by neocortical or thalamic rhythm generators. 52 Thus, we observed a disrupted FC in the α band that is consistent with a cortical hyper-responsivity typically found in migraine 14,53 as an expression of an underlying "thalamocortical dysrhythmia," 54 in which a deficient thalamocortical drive leads to a dysfunction of both inhibitory and excitatory cortical neurons. 55 Furthermore, some studies supported the hypothesis that α-FC disruption is related to the involvement of ascending and/or cortical cholinergic systems in neurodegenerative disorders.…”
Section: Networksupporting
confidence: 77%
“…Therefore, an excessive alpha desynchronisation could lead to an increased amplification of sensory signals that, in turn, could cause the visual disorders subjectively reported by patients. A recent work reinforces this interpretation [69], as it showed that migraine patients have both significantly lower alpha power before stimulus presentation than controls, and significantly higher alpha desynchronisation after the stimulus onset.…”
Section: Excitatory-inhibitory Imbalance and Sensory Processingmentioning
confidence: 68%
“…There is also evidence for differences in the synchronization of activity in the alpha band between a mixed migraine group (MO and MA) and controls during visual stimulation. Fong et al [ 69 ] demonstrated that migraineurs had significantly less posterior alpha power prior to the onset of the stimulus relative to controls. Moreover, migraineurs had significantly greater poststimulus alpha desynchronisation.…”
Section: Differences In Alpha-band Oscillationsmentioning
confidence: 99%